PEMENUHAN HAK ATAS PENDIDIKAN TERHADAP ANAK BINAAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS 1 BLITAR - Zahrah, Halimatuz; Pasu Marganda Hadiarto Purba, Iman (Kajian Moral dan Kewarganegaraan, 2024)
This study aims to determine the fulfillment of the right to education for foster children at the Blitar Class 1 Child Special Development Institution and its supporting and inhibiting factors. This research is a descriptive qualitative research. The data sources used are primary and secondary data. Primary data collection and secondary data. Data is collected through interviews and documentation. The results showed that the implementation of the right to education for foster children in special coaching institutions for children has not been fully fulfilled. However, efforts to implement education continue to be carried out as well as possible considering the importance of education for children who are serving a criminal period. Based on John Rawls' theory of justice, this study found that equality and distributive justice have not been fully realized. This research provides suggestions for the government to improve education policies and practices that are more equitable and inclusive for children who are in conflict with the law.